2015
DOI: 10.1039/c5ra13233a
|View full text |Cite
|
Sign up to set email alerts
|

LaPO4-coated Li1.2Mn0.56Ni0.16Co0.08O2 as a cathode material with enhanced coulombic efficiency and rate capability for lithium ion batteries

Abstract: Layered Li[Li0.2Mn0.56Ni0.16Co0.08]O2 porous microspheres have been successfully synthesized by a urea combustion method, and then coated with appropriate amount of LaPO4via a facile chemical precipitation route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The lattice spacing is around 0.47 nm which correspond to (003) planes of the rhombohedral phase (R 3m). 28,41 Elemental mapping images in Fig. 3(d-g) show the distribution of Ni, Mn, Co, and Zr in 1.5 wt% ZrO 2 coated NMC.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lattice spacing is around 0.47 nm which correspond to (003) planes of the rhombohedral phase (R 3m). 28,41 Elemental mapping images in Fig. 3(d-g) show the distribution of Ni, Mn, Co, and Zr in 1.5 wt% ZrO 2 coated NMC.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…[25][26][27] To address these issues, several strategies have been widely adopted including surface coatings of active materials, elemental doping on Ni, Mn or Co sites and tailoring the particle morphology. [6][7][8]12,[28][29][30][31][32][33] Amongst them, the surface coating of active materials has been widely accepted and employed to improve the performance of these materials. Several coating materials such as Al…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] In this regard, multifarious modification approaches, such as doping and surface coating, have been intensively investigated. ), metal phosphates (AlPO 4 , [28] LaPO 4 , [29] Li 3 PO 4 , [30] FePO 4 /Li 3 PO 4 , [31] Li-Mn-PO 4 , [32] etc. [17][18][19] From this viewpoint, metal fluorides (FeF 3 , [20] MOF, [21,22] AlF 3 , [23,24] etc.…”
mentioning
confidence: 99%
“…10 The LaPO 4 surface coating of NVPF was performed according to the procedure described in Refs. [21,22] with minor changes (see Materials and Methods). Based on the XRD results ( Figure 1) and the quantitative phase analysis of the coated sample (hereinafter referred as NVPF/LPO) using the Rietveld method (Table 1), it was found that the as-obtained composite material contains only two phases: Na 3 V 2 (PO 4 ) 2 F 3 and LaPO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…There are some publications devoted to the use of LaPO 4 as a coating material to increase the high-rate capability of the lithium-rich cathode materials. However, the improvement was related to the protective activity of LaPO 4 from the electrode-electrolyte interaction [21,22]. On the other hand, some authors associate it with the increase in electrical conductivity due to the high ionic conductivity of LaPO 4 [23], but this statement is contradictory [24].…”
Section: Resultsmentioning
confidence: 99%